2017
DOI: 10.1097/dcr.0000000000000926
|View full text |Cite
|
Sign up to set email alerts
|

The American Society of Colon and Rectal Surgeons Clinical Practice Guidelines for the Treatment of Colon Cancer

Abstract: The American Society of Colon and Rectal Surgeons is dedicated to ensuring high-quality patient care by advancing the science, prevention, and management of disorders and diseases of the colon, rectum, and anus. The Clinical Practice Guidelines Committee is composed of society members who are chosen because they have demonstrated expertise in the specialty of colon and rectal surgery. This committee was created to lead international efforts in defining quality care for conditions related to the colon, rectum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
198
1
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(223 citation statements)
references
References 201 publications
2
198
1
22
Order By: Relevance
“…While a number of international consensus guidelines support the role of CRS and HIPEC in the treatment of isolated CRPM [19,20], it must be noted that most of the data supportive of CRS and HIPEC is in the form of cohort studies that report a median survival of 30-58 months [7][8][9][10] with a paucity of randomised data [4]. Furthermore, CRS and HIPEC are offered to selected cases, while systemic chemotherapy is offered to a more unselected cohort.…”
Section: Discussionmentioning
confidence: 99%
“…While a number of international consensus guidelines support the role of CRS and HIPEC in the treatment of isolated CRPM [19,20], it must be noted that most of the data supportive of CRS and HIPEC is in the form of cohort studies that report a median survival of 30-58 months [7][8][9][10] with a paucity of randomised data [4]. Furthermore, CRS and HIPEC are offered to selected cases, while systemic chemotherapy is offered to a more unselected cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Интраоперационная стратегия включала использование минимально травматизирующих хирургических методик по принятым стандартам [5]. Оптими- Непосредственное участие госпитальной службы в интраоперационных мероприятиях минимально, однако каждый ее член ознакомлен с деталями работы хирургической команды в операционной.…”
Section: Sechenov First Moscow State Medical University Of Healthcareunclassified
“…the need for stoma creation is lower with SEMS plus elective surgery than with emergency surgery. 6,7 Initial endoscopic SEMS decompression has been recommended by several bodies such as the American Society of Colon and Rectal Surgeons, 8 National Comprehensive Cancer Network, 9 World Society of Emergency Surgery, 10 and Eastern Association for the Surgery of Trauma. 11 A retrospective study reported worse overall survival with SEMS and elective surgery than with emergency surgery in patients with left-sided malignant colon obstruction.…”
mentioning
confidence: 99%